2021
DOI: 10.3390/f12111562
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Carbon Stocks in Afforested Agricultural Land in Lithuanian Hemiboreal Forest Zone

Abstract: In the context of the specificity of soil organic carbon (SOC) storage in afforested land, nutrient-poor Arenosols and nutrient-rich Luvisols after afforestation with coniferous and deciduous tree species were studied in comparison to the same soils of croplands and grasslands. This study analysed the changes in SOC stock up to 30 years after afforestation of agricultural land in Lithuania, representing the cool temperate moist climate region of Europe. The SOC stocks were evaluated by applying the paired-site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 57 publications
(104 reference statements)
0
12
0
Order By: Relevance
“…In addition, in this case the effect of former land use had been long lasting. In a study carried out in Lithuania the average bulk density of fine (<2 mm) soil in the 0–30 cm layer was found to be higher in croplands compared to afforested areas (20–30 years after afforestation) and grasslands [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in this case the effect of former land use had been long lasting. In a study carried out in Lithuania the average bulk density of fine (<2 mm) soil in the 0–30 cm layer was found to be higher in croplands compared to afforested areas (20–30 years after afforestation) and grasslands [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, after several years, the accumulation of SOC reaches a level comparable to non-forested soils, and eventually, several decades after the afforestation process the SOC stock begins to increase more rapidly. Nevertheless, studies indicate that achieving the SOC levels found in natural forests requires a significant amount of time [ 15 , 16 , 17 ]. Furthermore, frequently significant translocation of SOC was observed within the soil profile, with a decrease in SOC and nitrogen (N) in deeper soil layer compensated by an increase in upper soil layer [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most areas were characterized by low APD (<0.051 Mg ha −1 ) and AKD values (<0.82 Mg ha −1 ), while several high-APD or high-AKD "points" were sporadically scattered across the South Dump (Figure 4). Numerous studies have explored the effects of afforestation on soil nutrient stocks in natural ecosystems [14,18,20,54,55]. It has remained controversial about the specific influence of afforestation on the evolution of soil nutrient stocks and different studies might draw different conclusions due to the comprehensive influence of climate, topography, and geological background [20].…”
Section: Semi-variogram Analysesmentioning
confidence: 99%
“…Over a different period, the afforestation of arable land impacts higher C stocks via C sequestration in tree biomass; input of litterfall and subsequent development of forest floor result in higher soil organic carbon (SOC) reserves in forests compared to croplands. In the afforested sites, soil organic matter tends to accumulate more intensively, and the C sequestration in the forest floor is determined [1,7,8]. In the longer term, C sequestration is associated with the C content in the mineral topsoil layers.…”
Section: Introductionmentioning
confidence: 99%
“…However, C content in mineral soils does not change in the first decades or even decreases following afforestation [13]. Recent studies on afforestation conducted in the region indicated that the new forest plantations established on agricultural land did not cause a significant increase in SOC stocks in the mineral 0-30 cm topsoil during the first 30 years period [8,14]. Analysis of the relationship between soil tillage technologies and changes in SOC showed that C stocks increase below the plough layer [15].…”
Section: Introductionmentioning
confidence: 99%